DESIGN PLANNING OF FLOOD CONTROL BUILDING DUE TO THE COLLAPSE OF PAMUKKULU DAM, TAKALAR DISTRICT, SOUTH SULAWESI - Rizki Pratama Santosa, Donny
Dambreak due to extreme weather is difficult to predict and anticipate, so the casualties and losses incurred will be large. Moreover, no dam is free from the potential to break. Of course, Pamukkulu Dam in Takalar Regency is no exception. This research examines the causes, impacts, and disaster management efforts of the Pamukkulu Dam breach in Takalar District, South Sulawesi, Indonesia. Extreme weather was used as the cause of the Pamukkulu Dam breach because it is likely to cause the greatest loss to Takalar Regency. Probable Maximum Precipitation (PMP) is the largest rainfall that can occur in an area. PMP is determined using the Hersfield method. The inflow discharge used is Probable Maximum Flood (PMF). The sorting of Synthetic Unit Hydrograph (HSS) methods was carried out using the Creager method, with the selected method being ITB-1b. Simulation of Pamukkulu Dam collapse and flood distribution using HEC-HMS v.4.6.1 and HEC-RAS v.6.3.1 applications. Structural measures have a better effect in reducing losses due to large flood disasters. A disaster risk analysis was conducted to determine the areas where structural measures are prioritized. Pattalsang sub-district was chosen as the prioritized area because it has the highest risk index of 0.75. The area of flood inundation in Takalar Regency and settlements in Pattalsang Sub-district are 114.36 km2 and 2.54 km2, respectively. Eleven levee segments with a total length of 13.42 km and height varying from 3.21 m to 4.92 m successfully reduced flooding by 100% in Pattalsang sub-district settlements. The Geostudio 2018 R2 application was used to calculate the slope safety factor under earthquake and no earthquake conditions. By utilizing sheet pile, the levee levee is safe against conditions without earthquakes and without earthquakes. The construction of the levee has a Budget Cost of Rp. 351.1 billion. Preventive, corrective, and rehabilitative maintenance planning is carried out on the levee.